Efektivitas Metode Pembelajaran Berbasis STEAM terhadap Peningkatan Keterampilan Siswa MI/SD di Era Abad 21 - Akhmad Dalil Rohman; Muhammad Maskur Musa; Arina Nahdia Falkhah; Aan Fadia Annur (IBTIDA, 2022)
Education is an effort to prepare students through learning activities designed to help them actively develop their potential, abilities, and talents. This study aims to determine the effectiveness of the STEAM-based learning method in improving the skills of MI/SD students in the 21st-century era. The research method used is the library study method. Sources of information can be books, journals, ebooks, or other scientific articles. The results of this study are that along with the rapid development of technology due to the industrial revolution, the current industrial revolution 4.0 has brought changes to the joints of human life, including in the world of education. Students must be equipped with various 21st-century skills and be able to find various challenges of progress, science, and technology. So one of the emerging developmental movements is STEAM (Science, Technology, Engineering, Art, and Math) learning. The STEAM learning model is a learning innovation that can be applied at all levels of education. It is designed to equip students with various skills to face various changes in the world, including the challenges of scientific and technological advances in education.